The effects of cross-border acquisitions on firms' productivity in the EU - Wildmer Daniel Gregori; Maria Martinez Cillero; Michela Nardo (European Commission, 2021)
This study empirically investigates the extent to which firms in the European Union, once acquired through a cross-border acquisition, show different productivity levels as compared to those firms that have not been acquired. Our identification strategy relies on the combination of Propensity Score Matching and the Staggered Difference-in-Difference estimator, using firms' balance sheet for the years 2008-2018. We find that cross-border acquisitions decrease the productivity of the acquired firms, especially in the manufacturing and services sectors, as well as in less knowledge intensive activities. Firms targeted by acquirers originating in emerging market economies also decrease productivity of high-tech target firms.
Keywords: D24; F23; F60; G34; 330; Cross-border M&As; FDI; TFP; European Union; Propensity Score Matching; DiD